Levels of Murine, but Not Human, CXCL13 Are Greatly Elevated in NOD-SCID Mice Bearing the AIDS-Associated Burkitt Lymphoma Cell Line, 2F7 - Widney, Daniel P.; Olafsen, Tove; Wu, Anna M.; Kitchen, Christina M. R.; Said, Jonathan W.; Smith, Jeffrey B.; Peña, Guadalupe; Magpantay, Larry I.; Penichet, Manuel L.; Martinez-Maza, Otoniel (PloS one, 2013)
Currently, few rodent models of AIDS-associated non-Hodgkin's lymphoma (AIDS-NHL) exist. In these studies, a novel mouse/human xenograft model of AIDS-associated Burkitt lymphoma (AIDS-BL) was created by injecting cells of the human AIDS-BL cell line, 2F7, intraperitoneally into NOD-SCID mice. Mice developed tumors in the peritoneal cavity, with metastases to the spleen, thymus, and mesenteric lymph nodes. Expression of the chemokine receptor, CXCR5, was greatly elevated in vivo on BL tumor cells in this model, as shown by flow cytometry. CXCL13 is the ligand for CXCR5, and serum and ascites levels of murine, but not human, CXCL13 showed a striking elevation in tumor-bearing mice, with levels as high as 200,000 pg/ml in ascites, as measured by ELISA. As shown by immunohistochemistry, murine CXCL13 was associated with macrophage-like tumor-infiltrating cells that appeared to be histiocytes. Blocking CXCR5 on 2F7 cells with neutralizing antibodies prior to injection into the mice substantially delayed tumor formation. The marked elevations in tumor cell CXCR5 expression and in murine CXCL13 levels seen in the model may potentially identify an important link between tumor-interacting histiocytes and tumor cells in AIDS-BL. These results also identify CXCL13 as a potential biomarker for this disease, which is consistent with previous studies showing that serum levels of CXCL13 were elevated in human subjects who developed AIDS-lymphoma. This mouse model may be useful for future studies on the interactions of the innate immune system and AIDS-BL tumor cells, as well as for the assessment of potential tumor biomarkers for this disease.